Reorientasi Perguruan Tinggi Hukum Sebagai Professional School Berlandaskan Pancasila dalam Mencetak Penegak Hukum Berintegritas di Era Teknologi Informasi: Reorientation of Law Colleges as Professional Schools Based on Pancasila in Printing Law Enforcers with Integrity in the Age of Information Technology - Khairunissa, Vena Lidya; Baiquni, Muhammad Iqbal; Pratama, Albert Dicky (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The existence of law universities is very essential in producing law graduates who are expected to be able to become professional law enforcement officers. This is because the law college is the only educational institution that provides legal education both holistically and integrally. It is hoped that law graduates produced by law universities will be able to fill professional positions that are only carried out by professional law graduates such as prosecutors, advocates, curators, judges, and notaries. In reality, the goal of law colleges in producing professional law graduates has not been fully realized. There are still law graduates who are printed by law colleges who are considered to have failed to become professional law enforcers. In recent years, many law enforcers have doubted their integrity. Legal universities are responsible for producing law graduates with an image and integrity based on Pancasila. In addition to integrity issues, law universities are also required to encourage the development of national law in the era of information technology. Given, the process of development of the times is certainly unavoidable. This study aims to answer two problem formulations, namely: how are law universities as printers of professional and integrity law graduates based on Pancasila both in the education system and practice?; and, what is the role of law universities in the development of national law in the era of information technology? This paper uses a juridical-normative approach in providing an overview of law universities in producing law graduates with integrity in the era of information technology.